Maddewata As The Performing Art Of Bissu Oral Tradition In Bugis Soppeng Society - Suciaty Pratiwi; Arisal Arisal; Faisal Faisal (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2020)
The history of I La Galigo as a literary work of ancient Bugis has given many contributions towards world literature development both in oral and written forms. In the previous decades, there were a lot of talks about past traditions which still exist in society. Those traditions have received the attention of various experts especially anthropologist, sociologists and philologists. One form of traditions that still exists today is the Bissu oral tradition. In various translations of episode of I La Galigo, those explain many things about the existence of Bissu with sacred verses which are inseparable from one another. The form of a Bissu tradition which still survives today is something that has value and becomes a local cultural heritage that can be said to be global. This paper aims to describe the ritual performing art in Bissu activities which manifests in tradition, especially in Bugis Soppeng society. Activities in a Bissu tradition certainly contain various kinds of local wisdom values that are expected to contribute to build one's character.